Lot Sizing dengan Evolutionary Algorithm dan Excel Solver - Bisma, Muhammad Ardhya (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Lot Sizing is the process of determining the optimal number of product orders for each period by considering several factors, including demand uncertainty, fixed costs, quantity discounts and holding costs, with the aim of minimizing total costs. Evolutionary Algorithm (EA) is a metaheuristic that can be applied to various optimization problems, including Lot Sizing. Solver is an Excel Add-In for solving optimization problems. With the ability of Evolutionary Algorithm to tackle Lot Sizing and the Solver which is capable of running Evolutionary Algorithm, it can be concluded that solving Lot Sizing can be done using the Solver. For the case example in this research, Lot Sizing produced from the Evolutionary Algorithm and Solver requires a total cost of 62.090 Rubles.